The Influence of Profitability, Company Size and Investment Decisions on Firm Value in the LQ45 Index 2022-2024 - Angelica Al'maliki Saliha Maza; Sabrina Nur Azizah; Devi Febrianti (JAKUMA : Jurnal Akuntansi dan Manajemen Keuangan, 2025)
This study seeks to analyse the impact of profitability, company size, and investment decisions on the value of firms listed on the LQ45 index from 2022 to 2024. The technique employed is multiple linear regression analysis in IBM SPSS 25. The research gathered 60 data sets with a purposive sampling method. The findings indicated that profitability and investment decisions significantly influenced firm value. Simultaneously, the scale of the corporation exhibited little impact on its valuation. Based on these findings, companies seeking to increase their firm value should prioritize optimizing profitability and making strategic investment decisions. Furthermore, company size does not always reflect valuation performance, so management should focus on efficiency and added value rather than simply expanding scale.